Evaluation of different composite resin finishing and polishing protocols by confocal laser scan microscopy - Souza, Kayo Matheus Rodrigues de; Silva, Roberto Victor De Melo; Dias, Marlon Ferreira [UNESP]; Lins-Filho, Paulo Cardoso; Silva, Claudio Heliomar Vicente da; Guimarães, Renata Pedrosa (Universidade Estadual de Campinas, 2021)
Aim: This study aimed to analyze the influence of finishing and polishing (F/P) protocols on resin surface through roughness (Ra) values and laser scan microscopy observations. Methods: Forty-eight (n=48) resin specimens were sorted into four groups (n=12), according to the type of resin used: Filtek Z250 (Z250), Filtek Z350 (Z350), Filtek One Bulk Fill (BF), Filtek P60 (P60). The specimens were sorted into six groups according to the type of F/P system used (n=2/group): Control group, Diamond bur (KG Sorensen), Soflex Pop-On Discs (3M ESPE), Soflex Spiral (3M ESPE), Dura Gloss (American Burs), and Praxis (TDV). Results: The highest roughness values (Ra) were attributed to BF group for all F/P systems, except for the Soft-Lex PopOn discs. The Soft-Lex PopOn, Spiral, and Praxis discs presented a better performance for the surface treatment of the tested composite resins. Regardless of the restorative material, the use of diamond bur or single-step abrasive rubber (Dura Gloss) were associated with the highest Ra values. Conclusion: The effect of F/P systems on Ra is material-dependent and instrument or system-dependent.
Keywords: Composite resins. Dental materials. Dental polishing